STRATEGI PERENCANAAN MANAJEMEN KOMUNIKASI DALAM PENERIMAAN MAHASISWA BARU DI INTERNATIONAL WOMEN UNIVERSITY BANDUNG - Hamidah (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2025)
This study examines communication management planning in the new student admission process at International Women University (IWU) as an effort to enhance the effectiveness of promotional activities and increase prospective students’ interest. In the context of increasingly intense competition among higher education institutions, a well-planned and systematic communication strategy has become a crucial factor in achieving admission targets. This research employs a qualitative approach, with data collected through in-depth interviews, observation, and documentation. The research informants include members of the management team, public relations officers, and administrative staff directly involved in the student admission process. Data were analyzed descriptively to identify communication patterns, implemented strategies, and challenges encountered. The findings indicate that IWU has implemented a comprehensive communication planning process, encompassing situation analysis, target audience identification, selection of communication media, program implementation, and evaluation. The media utilized include social media platforms, the official website, brochures, and direct promotional visits to schools. These strategies have proven effective in increasing institutional visibility and expanding information outreach to prospective students. However, the implementation still faces challenges, particularly in terms of limited human resources and promotional budget constraints. This study concludes that structured communication management planning plays a significant role in supporting the success of new student admissions at IWU. Therefore, strengthening strategic planning, enhancing collaboration, and optimizing the use of digital technology are recommended for future development.